PENGUATAN STRATEGI BRANDING UMKM PRODUKSI TELUR ASIN DI DESA SUKAMAJU KECAMATAN CIANJUR KABUPATEN CIANJUR - Dina, Dina (Indonesian Community Service and Empowerment Journal (IComSE), 2024)
Micro, Small and Medium Enterprises (MSMEs) business people often still focus on trading activities and tend to ignore the importance of branding and product legality. This phenomenon can be caused by several factors, such as lack of knowledge, selfish attitude, or closedness to new ideas and a tendency to be quickly satisfied. In the context of marketing communications, branding and product legality have a vital function as a means of instilling a positive image in the minds of consumers. Therefore, understanding the importance of branding and product legality is very necessary for business actors, because this aspect is one of the key factors so that MSME products can continue to be remembered by the public or consumers in the long term. One of the MSMEs in Sukamaju Village is "Sukarasa Salted Eggs," which operates in the field of salted egg production. This Community Service activity is focused on introducing and applying branding and product legality to MSMEs in Sukamaju Village, especially the Bu Dede/Pa Ende Salted Egg MSMEs. This activity is carried out through various methods, including MSME surveys, outreach, mentoring, and submission of achievement results. The main obstacle faced by MSMEs is the lack of optimal product marketing. Therefore, this Community Service aims to introduce and apply the concept of branding and legality to products. It is hoped that this activity will have a positive impact on the development of Sukarasa bu dedeh/Pa Ende Salted Egg Production MSMEs, increase the competitiveness of their products in the market, and ensure the smooth operation of their business. Key words: UMKM, Branding, Product Legality